2020
DOI: 10.1080/19490976.2020.1770666
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines against gastroenteritis, current progress and challenges

Abstract: Enteric viral and bacterial infections continue to be a leading cause of mortality and morbidity in young children in low-income and middle-income countries, the elderly, and immunocompromised individuals. Vaccines are considered an effective and practical preventive approach against the predominantly fecal-to-oral transmitted gastroenteritis particularly in the resource-limited countries or regions where implementation of sanitation systems and supply of safe drinking water are not quickly achievable. While v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 263 publications
(271 reference statements)
0
15
0
Order By: Relevance
“…Additionally, L-DBF provides the much-desired crossprotection that is lacking with traditional LPS based vaccines including whole killed, live-attenuated and O-antigen based vaccines that are considered serotype specific. In contrast, the T3SS proteins IpaB and IpaD are conserved among all serotypes and have been considered attractive target antigens in subunit vaccine development (30,31). Early studies showed that DBF with dmLT administered IN protected mice against S. flexneri, S. sonnei and S. dysenteriae.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, L-DBF provides the much-desired crossprotection that is lacking with traditional LPS based vaccines including whole killed, live-attenuated and O-antigen based vaccines that are considered serotype specific. In contrast, the T3SS proteins IpaB and IpaD are conserved among all serotypes and have been considered attractive target antigens in subunit vaccine development (30,31). Early studies showed that DBF with dmLT administered IN protected mice against S. flexneri, S. sonnei and S. dysenteriae.…”
Section: Discussionmentioning
confidence: 99%
“…An additional concern limiting treatment options is the evolution of multidrug-resistant Shigella strains. Thus, control measures have primarily focused on development of vaccines that include whole -cells killed, live attenuated and various subunit-based Shigella vaccines [4][5][6][7]. Following vaccination or infection the ability to measure the immune response, using reproducible and technologically simple methods is critical, particularly if evaluating a vaccine candidate in a resource limited region.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these drawbacks, advancements have been achieved, with four candidate vaccines having reached the stage of clinical development. While several review papers were published recently, giving systematic overviews on the preclinical developments of various norovirus vaccine candidates [12][13][14][15][16][17], this short article focuses on the current advances in clinical evaluations of four vaccine candidates.…”
Section: Introductionmentioning
confidence: 99%